Brain MRI findings in patients with post COVID-19 condition: frequency and longitudinal changes in a nationwide cohort study - Furevik, Liv Lygre; Lapina, Oksana; Lindland, Elisabeth Stokke; Høgestøl, Einar August; Geier, Oliver Marcel; Devik, Kristina; Farmen, Anette Huuse; Flemmen, Heidi Øyen; Harbo, Hanne Flinstad; Morsund, Åse Hagen; Novotny, Vojtech; Ofte, Hilde Karen; et al. (Frontiers in Neurology, 2025)
BackgroundProlonged neurological symptoms following COVID-19 are common, yet few longitudinal studies describe brain MRI findings in this patient group. The use of contrast enhanced sequences is particularly lacking. We address this knowledge gap by reporting the frequency and longitudinal changes in brain MRI findings among patients with post COVID-19 condition exhibiting neurological symptoms.MethodsThis prospective multicenter study included 140 adult patients referred for persistent neurological symptoms following COVID-19. Brain MRI was performed at both 6 and 12 months after infection onset, reporting white matter hyperintensities, cerebral microbleeds, and additional pathological findings including contrast enhancement. White matter hyperintensities were compared with a healthy control group.ResultsThe prevalence of white matter hyperintensities was comparable to healthy controls, and microbleeds were found at rates comparable to population studies, with longitudinal changes being infrequent. Lesions consistent with inflammation or demyelination were present in 4% (5/120) of patients at 6 months. Cranial nerve enhancement was found in 7% (7/94) of patients, persisting up to 12 months, predominantly affecting the oculomotor nerve. However, enhancement occurred without clinically detected ocular muscle paresis.ConclusionOur findings indicate that brain MRI primarily serves to exclude differential diagnoses in post COVID-19 condition, with limited clinical benefit of repeated imaging in the absence of new symptoms. However, signs of long-term inflammatory processes can be observed, and detection is improved by contrast enhanced sequences.